Terrorism in different parts of the world: Comparison of terrorist organizations ETA, IRA and PKK - Özer, Mehmet (Cappadocia Journal of Area Studies, 2022)
Terror has emerged in almost all regions of the world from the past to the present and has exposed countries and societies to violent acts for many years. Each terrorist organization has different dynamics. The aim of this study is to compare the ETA, IRA and PKK terrorist organizations, which Spain, England and the Republic of Turkey have fought for many years, in terms of their emergence and disintegration processes as regional terrorist movements and their methods of action. For this purpose, the emergence processes of these organizations in the first part of the study, the methods of action in the second part, the dissolution processes of the terrorist organizations ETA and IRA in the third part and the situation after the capture of the leader of the PKK terrorist organization were explained, and in the conclusion part, the organizations were compared within the scope of these three criteria.